The Role of the International Organization for Migration (IOM) in Addressing Human Trafficking in Edo State, Nigeria (2017-2019) - Annisa Ramadhani Santosa; Maulana Rifai; Prilla Marsingga (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
Human trafficking remains a serious transnational crime and human rights violation, particularly in Nigeria, where Edo State has been identified as the main hub for trafficking networks targeting Europe. The complexity of trafficking in this region is intensified by the use of juju rituals as a cultural–spiritual mechanism to control victims psychologically. This study aims to analyze the role of the International Organization for Migration (IOM) in addressing human trafficking in Edo State, Nigeria, during the period 2017–2019. The research employs a qualitative approach using a case study design, with data collected from secondary sources such as official IOM reports, Nigerian government documents, international organization publications, and relevant academic literature. Data were analyzed using the 4P framework, prevention, protection, prosecution, and partnership within the perspective of neoliberal institutionalism. The findings indicate thatIOM played a multidimensional role through prevention programs focused on awareness campaigns and livelihood support, protection through Assisted Voluntary Return and Reintegration (AVRR) programs, prosecution by strengthening the capacity of law enforcement and judicial institutions, and partnership through multi-level cooperation with governmental, non-governmental, and international actors. A key finding of this study is IOM's facilitation of culturally sensitive interventions by integrating the spiritual declaration of the Oba of Benin, which annulled juju oaths binding trafficking victims. This approach demonstrates IOM's institutional adaptability in addressing locally rooted trafficking mechanisms. The study concluded that IOM made a significant contribution to the reduction of trafficking cases from Edo State during the study period, although its effectiveness was influenced by external factors and structural limitations.